Web and Android-based Test Application Development and its Implementation on Final Semester Examination - Ambiyar, -; Panyahuti, -; Devega, Army Trilidia; Islami, Syaiful (Society of Visual Informatics, 2024)
This research aims to revolutionize the examination process in vocational schools by developing the FlyExam application, an Android-based test platform derived from improvements to the TCExam interface. The core goal was to create a powerful, easy-to-use, and effective tool for semester assessment. Following a Research and Development (R&D) approach, this research uses a 4D model: Define, Design, Develop, and Disseminate. Validation procedures require expert evaluation of the technical aspects and usability of the application. At the same time, practicality is assessed through engagement with students and teachers, and effectiveness is measured by student performance. Expert reviews and user feedback confirm the validity and practicality of the application. During implementation, the LAN network topology proved to be a conducive environment for conducting semester exams, increasing the efficiency and reliability of the testing process. The integration of TCExam and FlyExam on mobile devices shows the potential of transitioning from traditional paper-based exams to digital platforms, offering greater flexibility and accessibility. Future research efforts could explore FlyExam's scalability and adaptability in various educational contexts and its long-term impact on assessment practices and academic outcomes. Additionally, ongoing improvements based on user feedback can lead to further improvements and the incorporation of new features, ensuring FlyExam remains relevant and effective in meeting evolving vocational education needs. In summary, the development of FlyExam represents significant progress in the modernization of assessment methodology, with the potential to simplify the process and improve the learning experience in vocational schools.